2013
DOI: 10.1007/s10147-013-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

A single-center analysis of the survival benefits of adjuvant gemcitabine chemotherapy for biliary tract cancer

Abstract: Adjuvant gemcitabine chemotherapy for BTC may be effective, particularly for patients with stage III and ICC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 20 publications
(18 reference statements)
0
33
0
Order By: Relevance
“…We previously reported the significance of fluorine-18 fluorodeoxyglucose positron emission tomography ( 18 FDG-PET) [10] and adjuvant chemotherapy [11] for ICC management. 18 FDG-PET is predictive of lymph node metastasis and ICC recurrence after surgical resection and is useful for identifying patients at high risk for recurrence [10].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the significance of fluorine-18 fluorodeoxyglucose positron emission tomography ( 18 FDG-PET) [10] and adjuvant chemotherapy [11] for ICC management. 18 FDG-PET is predictive of lymph node metastasis and ICC recurrence after surgical resection and is useful for identifying patients at high risk for recurrence [10].…”
Section: Introductionmentioning
confidence: 99%
“…9 While these previous studies were valuable in exploring the potential role of adjuvant therapy, most data on the topic of adjuvant therapy for GBC suffer from small, heterogeneous patient populations that mix GBC with extra-and intrahepatic cholangiocarcinoma, as well as include patients who have undergone nononcologic resections. [10][11][12][13] Given this, we sought to evaluate the role of adjuvant CTx and cXRT among patients undergoing curative intent surgical resection for GBC using a large, multicenter, national collaborative database. Specifically, the objective of the current study was to define those factors associated with receipt of adjuvant therapy, as well as evaluate the relative treatment benefit of CTx/cXRT versus surgery alone using propensity-matched analysis of patients undergoing curative intent resection of GBC.…”
mentioning
confidence: 99%
“…Takada et al demonstrated that patients with GBC receiving adjuvant therapy consisting of mitomycin C and 5-FU after surgery had an improved overall survival (22). Some have recommended adjuvant chemotherapy and chemoradiotherapy after surgery for biliary carcinoma, as shown in Table III (21,24,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). However, the results of adjuvant external-beam radiation therapy with concurrent 5-FU treatment were unsatisfactory, with a 5-year survival rate of less than 40% (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant gemcitabine alone was expected to improve the prognosis of patients with GBC after non-curative resections (34). Another study recommended that adjuvant gemcitabine alone might be effective in selected patients with either stage III biliary carcinoma or IHCC (33). Furthermore, adjuvant gemcitabine and S-1 combination chemotherapy has been introduced for its synergistic antitumour effect, and the regimen provided the best clinical impact for patients with UICC stage IIA/B biliary carcinoma, with a 57% survival rate at 5 years after aggressive surgery.…”
Section: Discussionmentioning
confidence: 99%